Osmotic dehydrated raspberries: changes in physical and bioactive compounds - Sette, Paula Andrea (2015)
Raspberries are very labile fruits that have a short postharvest life; therefore, there is a need to develop alternative storage and processing methods for extending their shelf-life. The effect of wet (WI) and dry (DI) sucrose infusions (aw= 0.85) on color and bioactive compounds of raspberries has been studied. Additives were included: citric acid, sodium bisulphite or both. Moisture content decreased from 85% (w/w) for control fruit to approx. 51% (w/w) for infused samples. The shrinkage of fruits was approx. 27% and 46% after WI and DI, respectively. Total polyphenols and anthocyanins content were significantly reduced in fruits during osmotic dehydration mainly due to the dilution effect to the medium. However, the total quantity of polyphenols in fruits + syrup system increased approx. 70% after infusions. No major color changes occurred, except for WI-bisulphite treatment. The proposed infusion dehydration methods may be considered an alternative to produce shelf-stable products based on raspberries, with an improved quality in terms of color and fresh-like characteristics retention.